Transformasi Pembelajaran Sejarah Melalui Implementasi LMS Microsoft Teams di SMA Negeri 1 Lumajang - Kartika, Adelea Wardah; Sayono, Joko; Widiadi, Aditya Nugroho (Cetta: Jurnal Ilmu Pendidikan, 2025)
Digital transformation in education does not merely introduce new tools or media, but demands a fundamental paradigm shift in teaching approaches, including in history education, which has traditionally been associated with lectures and rote memorization. Responding to this dynamic, the present study aims to explore how the implementation of a Learning Management System (LMS), specifically Microsoft Teams, has transformed the strategy of history teaching at SMA Negeri 1 Lumajang from conventional face-to-face methods to a more adaptive and participatory digital learning model. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation to portray the process and impact of LMS usage comprehensively. The findings reveal that Microsoft Teams functions not only as a technical support tool, but also as a learning environment that strengthens the teacher’s role as an active facilitator while encouraging students to become independent and digitally literate learners. The LMS enhances learning engagement through features such as discussion channels, digital assignments, and organized access to instructional materials. Interestingly, even after the return to face-to-face learning, many teachers continue to utilize the LMS to support a more structured and flexible hybrid learning model. Nevertheless, challenges such as limited access to devices, connectivity gaps, and varying levels of digital competence remain obstacles that require resolution through ongoing training, infrastructure support, and consistent institutional policies. This study concludes that the LMS is not merely a reactive solution to crisis conditions, but has become a pedagogical foundation for building sustainable, contextual, and future-oriented history learning practices in line with 21st-century educational demands.